2020
DOI: 10.1371/journal.pntd.0008125
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine supplementation improves the efficacy of miltefosine treatment for visceral leishmaniasis

Abstract: BackgroundThe disturbance of host metabolic pathways by Leishmania parasites has crucial consequences for the activation status of immune cells and the outcome of infection. Glutamine has been described as an immunomodulatory amino acid, yet its role during Leishmania infection is still unknown.Visceral leishmaniasis is a life threatening neglected tropical disease affecting around 500,000 and killing 50,000 individuals a year. Despite its obligatory dependence on host cell metabolism and the lack of effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
5
24
0
Order By: Relevance
“…These findings contrast with the metabolomic profiling of L. amazonensis -infected macrophages, which showed increased glutamine levels [ 22 ]. A recent study in mice infected with L. donovani, however, showed heightened glutamine consumption with infection and a role of glutamine supplementation in clearing parasite load [ 37 ], which concur with our findings. Future studies should aim to look at the specific functional role of the glutamine metabolism in L. major infection.…”
Section: Discussionsupporting
confidence: 93%
“…These findings contrast with the metabolomic profiling of L. amazonensis -infected macrophages, which showed increased glutamine levels [ 22 ]. A recent study in mice infected with L. donovani, however, showed heightened glutamine consumption with infection and a role of glutamine supplementation in clearing parasite load [ 37 ], which concur with our findings. Future studies should aim to look at the specific functional role of the glutamine metabolism in L. major infection.…”
Section: Discussionsupporting
confidence: 93%
“…During cellular stress, such as nutrient starvation and catabolic stress after trauma, surgery, infection, sepsis, or cancer cachexia, blood glutamine levels are severely decreased 144 . Under these conditions, several studies have reported that glutamine supplementation can offer a therapeutic approach for these critical illnesses [145][146][147] . Glutamine has been considered an immunomodulatory amino acid in several disease states, yet the mechanisms underlying the therapeutic effects of glutamine supplementation in critical illness remain poorly understood.…”
Section: Glutamine Metabolism Upon Cellular Stressesmentioning
confidence: 99%
“…Glutamine has been known to modulate immune response and play essential role for the control of L. donovani infection to macrophages. The gene of glutamine metabolism have been found to be upregulated in macrophages infected by L. donovani , as revealed by transcriptomic analysis ( Ferreira et al., 2020 ). It is known that the protein expression is more when the gene integration happens in the genome, as compared to episomal addition.…”
Section: Discussionmentioning
confidence: 99%